Synthesis and Characterization of Boron Nitride Thin Films Deposited by High-Power Impulse Reactive Magnetron Sputtering - Vytautas Stankus; Andrius Vasiliauskas; Asta Guobienė; Mindaugas Andrulevičius; Šarūnas Meškinis (Molecules)
In the present research, hexagonal boron nitride (h-BN) films were deposited by reactive high-power impulse magnetron sputtering (HiPIMS) of the pure boron target. Nitrogen was used as both a sputtering gas and a reactive gas. It was shown that, using only nitrogen gas, hexagonal-boron-phase thin films were synthesized successfully. The deposition temperature, time, and nitrogen gas flow effects were studied. It was found that an increase in deposition temperature resulted in hydrogen desorption, less intensive hydrogen-bond-related luminescence features in the Raman spectra of the films, and increased h-BN crystallite size. Increases in deposition time affect crystallites, which form larger conglomerates, with size decreases. The conglomerates’ size and surface roughness increase with increases in both time and temperature. An increase in the nitrogen flow was beneficial for a significant reduction in the carbon amount in the h-BN films and the appearance of the h-BN-related features in the lateral force microscopy images.